2024
DOI: 10.31083/j.fbl2905190
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathophysiological Relevance of Nitric Oxide Synthases (NOS) in Retinal Blood Vessels

Adrian Gericke,
Francesco Buonfiglio

Abstract: Nitric oxide synthases (NOS) are essential regulators of vascular function, and their role in ocular blood vessels is of paramount importance for maintaining ocular homeostasis. Three isoforms of NOS—endothelial (eNOS), neuronal (nNOS), and inducible (iNOS)—contribute to nitric oxide production in ocular tissues, exerting multifaceted effects on vascular tone, blood flow, and overall ocular homeostasis. Endothelial NOS, primarily located in endothelial cells, is pivotal for mediating vasodilation and regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 136 publications
0
1
0
Order By: Relevance
“…On the other hand, nNOS is primarily expressed in nerve terminals, skeletal muscle, and to a lesser extent in vascular SMCs, and its contribution to systemic vascular NO production is typically less significant compared to eNOS 69 . Our findings also align with previous studies that have demonstrated enhanced eNOS activity in the absence of Cav1, reinforcing the hypothesis that eNOS is the main source of the excessive NO production observed in MFS/Cav1KO mice 70,71 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, nNOS is primarily expressed in nerve terminals, skeletal muscle, and to a lesser extent in vascular SMCs, and its contribution to systemic vascular NO production is typically less significant compared to eNOS 69 . Our findings also align with previous studies that have demonstrated enhanced eNOS activity in the absence of Cav1, reinforcing the hypothesis that eNOS is the main source of the excessive NO production observed in MFS/Cav1KO mice 70,71 .…”
Section: Discussionmentioning
confidence: 99%